Market Contagion: Evidence from the Panics of 1854 and 1857 - Kelly, Morgan; Gráda, Cormac Ó (American Economic Review, 2000)
To test a model of contagion—where individuals hear some bad news and communicate it to their acquaintances, who then pass it on, leading to a market panic—requires a knowledge of the information networks of participants, something hitherto unavailable. For two panics in the 1850's this paper examines the behavior of Irish depositors in a New York bank. As recent immigrants, their social network was determined largely by their place of origin in Ireland, and where they lived in New York. During both panics this social network turns out to be the prime determinant of behavior. (JEL G21, N21)